Legal Protection and the Problem of Accessibility for Diffable: A Comparative Study between Islamic Law and Indonesian Law - Sopyan, Yayan (Mazahib, 2019)
As a Nation of Laws, every citizen is guaranteed to their freedom, being admitted and protected to their dignity, and also possesses the same position in the presence of law. Indonesia acknowledges and protects the human rights of its citizens without differentiating their background as enshrined in the 1945 Constitution. Part of Indonesian citizens is diffable (different in ability) group and they are supposed to have the same rights, responsibility, and positions as others. However, they have physical and psychological limitations and are considered to have difficulties to access public facilities without giving them the proper access. Accessibility is an important role to actualize the parity of opportunities in every aspect of life. It is an easiness provided for diffable people to achieve the same chance. In Islam, the issue of diffability has been discussed too which is drawn from the Qur’an and Hadith as the major source of Sharia. This article aims to point out the intersection between Islamic law and Indonesian law in providing concerns towards diffable people to obtain their rights and to observe how the legal protection to accessibility for diffable has been implemented. It finds that in the normative order, both Islamic and Indonesian law have provided adequate attention and protection for diffable people. Nevertheless, the means to provide access for them is yet to be optimal. The causes are: inconsistency to properly implement the law, incomplete facilities, and the unfriendly behavior and culture towards people with disabilities.Keywords: Islamic Law, Indonesian Law, Diffable, Accessibility